Performance of a low-cost optical particle counter (Alphasense OPC-N3) in estimating size-resolved dust emission flux using eddy covariance - S. Dupont; E. Lamaud; M. R. Irvine; J.-M. Bonnefond; A. González-Romero; A. González-Romero; A. Alastuey; C. González-Flórez; X. Querol; K. Kandler; M. Klose; C. Pérez García-Pando; et al. (Atmospheric Measurement Techniques)
The recent development of low-cost optical particle counters (OPCs) presents new opportunities for improving spatial coverage of particle concentration in the atmosphere as they are more affordable, compact, and energy efficient than traditional OPCs. In particular, these OPCs could improve our ability to quantify dust emissions in complex environments during aeolian soil erosion. The high-frequency sampling capacity (1 Hz) of some sensors may make them suitable for estimating dust emissions using the eddy-covariance method. Here, the capability of the low-cost OPC-N3 from Alphasense to estimate size-resolved dust flux using the eddy-covariance method is evaluated. During the Jordan Wind erosion And Dust Investigation (J-WADI) experiment, we tested one OPC-N3 against two traditional reference OPCs, the Promo and Fidas, from Palas GmbH. The N3 and Promo OPCs were located in close proximity to a sonic anemometer, enabling the correlation of dust concentration and vertical velocity fluctuations for estimating dust fluxes. Despite the high-temperature and dusty wind conditions of the campaign, the N3 monitored the dynamics and magnitude of dust concentration with reasonable precision. The turbulence characteristics of the dust concentration fluctuations measured by the N3, including variance, skewness, kurtosis, and energy spectrum, were similar to those from the Promo. However, the N3 flow rate exhibited variations under these outdoor conditions that affected the concentration of fine dust particles, and certain particles around 1 µm appeared to be misclassified in the upper size bin. After correcting the N3 dust concentration to address these discrepancies and after calibrating it against a reference OPC, the N3 accurately estimated the dust emission flux, with differences of less than 30 % compared to the reference OPC. Our results confirm the potential of low-cost OPCs for dust erosion research. Nonetheless, further evaluation of low-cost OPCs is still needed across different environments and weather conditions.